Meta-Analysis of The STEM Application Effect on Students' Creative Thinking - Aldilla, Endang; Asrizal, Asrizal; Usmeldi, Usmeldi (Indonesian Journal of Science and Mathematics Education, 2023)
21st century learning emphasizes mastery of knowledge through a STEM approach. This study aims to evaluate research that examines the effect of STEM implementation on students' creative thinking. The moderating variables considered were educational level, learning models, and learning materials. This study employs a meta-analysis method to collect quantitative data to calculate the effect size of each relevant study. The searched national and international journals were those recognized by ISSN and DOI between 2017 and 2023. The results of the study show that the STEM approach is effective at all levels of education, the STEM approach based on learning models (PjBL, PBL, and Inquiry) effectively improves students' creative thinking, and the STEM approach based on teaching materials are effectively applied to global warming material. It can be concluded that applying STEM can improve students' creative thinking skills. Future researchers are expected to analyze certain areas of STEM implementation or look at the long-term effects of creative thinking on students.